Indonesian nationalism discourse on YouTube video produced by young Chinese-Indonesians - Susilo, Daniel (Plaridel, 2021)
Access online through this link: https://www.plarideljournal.org/article/indonesian-nationalism-discourse-on-youtube-video-produced-by-young-chinese-indonesians